Great power security cooperation : arms control and the challenge of technological change - Kearn, David W. (Lexington Books, 2015)
"Focusing on the expected military impact of technological change and the capacity of states to confidently monitor the innovations of its neighbors, this book explains the conditions under which states may be able to successfully forge cooperative agreements that improve their security"--Provided by publisher.